Designing A Web-Based Employee Payroll Application: Case Study on One of The Raw Material Distributor Companies in West Java - Maulida, Nurul Fudla; Wahyudi, Heri (Journal of Economics, Management, and Entrepreneurship, 2023)
The fulfillment of the employees' payroll is a crucial task of the firm, ensuring the wellbeing of its workforce following a complete month of employment. The wage calculation system employed by a raw material distribution company in West Java currently relies on semi-computerized methods, specifically utilizing MS Excel for processing purposes. This approach is considered less efficient and susceptible to inaccuracies in its computations. This study aims to design and implement a system that can aid the organization in reducing computation errors. The author employs a qualitative descriptive methodology in their study. The author employs the OOSE (Object Oriented System Engineering) method as the chosen approach for development, emphasizing use cases. The employee payroll application was designed and implemented using the PHP programming language with the Laravel framework. The MySQL database was utilized for data storage. The anticipated outcome of the investigation into the employee payroll application is poised to provide the organization with improved efficiency and precision in processing employee wage calculations while concurrently mitigating the potential for data loss.